DNA damage response-related ncRNAs as regulators of therapy resistance in cancer - Gao, Ziru; Luan, Xinchi; Wang, Xuezhe; Han, Tianyue; Li, Xiaoyuan; Li, Zeyang; Li, Peifeng; Zhou, Zhixia (Frontiers in Pharmacology, 2024)
The DNA damage repair (DDR) pathway is a complex signaling cascade that can sense DNA damage and trigger cellular responses to DNA damage to maintain genome stability and integrity. A typical hallmark of cancer is genomic instability or nonintegrity, which is closely related to the accumulation of DNA damage within cancer cells. The treatment principles of radiotherapy and chemotherapy for cancer are based on their cytotoxic effects on DNA damage, which are accompanied by severe and unnecessary side effects on normal tissues, including dysregulation of the DDR and induced therapeutic tolerance. As a driving factor for oncogenes or tumor suppressor genes, noncoding RNA (ncRNA) have been shown to play an important role in cancer cell resistance to radiotherapy and chemotherapy. Recently, it has been found that ncRNA can regulate tumor treatment tolerance by altering the DDR induced by radiotherapy or chemotherapy in cancer cells, indicating that ncRNA are potential regulatory factors targeting the DDR to reverse tumor treatment tolerance. This review provides an overview of the basic information and functions of the DDR and ncRNAs in the tolerance or sensitivity of tumors to chemotherapy and radiation therapy. We focused on the impact of ncRNA (mainly microRNA [miRNA], long noncoding RNA [lncRNA], and circular RNA [circRNA]) on cancer treatment by regulating the DDR and the underlying molecular mechanisms of their effects. These findings provide a theoretical basis and new insights for tumortargeted therapy and the development of novel drugs targeting the DDR or ncRNAs.